Bioactive Oxidatively Truncated Phospholipids in Inflammation and Apoptosis: Formation, Targets, and Inactivation - McIntyre, Thomas M. (2012)
This report reviews structurally related phospholipid oxidation products that are biologically active where molecular mechanisms have been defined. Phospholipids containing polyunsaturated fatty acyl residues are chemically or enzymatically oxidized to phospholipid hydroperoxides, which may fragment on either side of the newly introduced peroxy function to form phospholipids with a truncated sn-2 residue. These truncated phospholipids not subject to biologic control of their production and, depending on the sn-2 residue length and structure, can stimulate the plasma membrane receptor for PAF. Alternatively, these chemically formed products can be internalized by a transport system to either stimulate the lipid activated nuclear transcription factor PPARγ or at higher levels interact with mitochondria to initiate the intrinsic apoptotic cascade. Intracellular PAF acetylhydrolases specifically hydrolyze truncated phospholipids, and not undamaged, biosynthetic phospholipids, to protect cells from oxidative death. Truncated phospholipids are also formed within cells where they couple cytokine stimulation to mitochondrial damage and apoptosis. The relevance of intracellular truncated phospholipids is shown by the complete protection from cytokine induced apoptosis by PAF acetylhydrolase expression. This protection shows truncated phospholipids are the actual effectors of cytokine mediated toxicity.